ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KREDIT MACET PADA KOPERASI SERBA USAHA (KSU) CREDIT UNION (CU) MITRA CHARITAS DI KELURAHAN WANAGON KABUPATEN MIMIKA - Simprosius M. Lanur; Ahmad Tomu (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the factors that influence bad debts in the Multipurpose Cooperative (KSU) Credit Union (CU) Mitra Charitas in Wanagon Village, Mimika Regency. The method used in this study is the associative method. Data collection techniques used in this study are observation and documentation. The analysis tools used in this study are descriptive statistics, Multiple Linear Regression, with data processing techniques using the Classical Assumption test and hypothesis, to analyze data using SPSS 25 Windows Software. The results of the study indicate that the amount of credit disbursed has a positive effect on bad debts, while the number of debtors has a negative effect on bad debts, and interest rates have a positive and insignificant effect on bad debts